Correlating transcranial arterial Doppler velocities with haematologic parameters and haemolytic indices of Nigerian children with sickle cell anaemia - Ismail, Anas (Ultrasound, 2019)
INTRODUCTION: Cerebral vasculopathy, elevated transcranial Doppler velocities and stroke are linked to excessive intravascular haemolysis in sickle cell anaemia. This study determined the prevalence and pattern of abnormal blood flow velocities in children with sickle cell anaemia from Northern Nigeria using transcranial Doppler and to correlate transcranial Doppler velocities with haematological and biochemical markers of haemolysis. METHODS: Full blood count, reticulocyte count, fetal haemoglobin and some selected biochemical markers of haemolysis of 100 children with sickle cell anaemia were determined at steady state. The time-averaged mean of maximal velocities in four major intracranial blood vessels was measured using non-imaging transcranial Doppler, which were then classified according to the stroke prevention in sickle cell disease trial protocol. A simple linear correlation between time-averaged mean of maximal velocities in the four major intracranial vessels as the dependent variable and haematological and biochemical markers of haemolysis as independent variables was also determined at the significance level of 0.05. RESULTS: Abnormal transcranial Doppler velocities, classified as high risk, were found in 3% of the studied patients; 11% had intermediate risk while 84% had standard risk. Most high velocities were detected in the middle cerebral artery. The time-averaged mean of maximal velocities of middle cerebral artery positively correlated with total white blood cell count, absolute neutrophil count, platelet count, reticulocyte count, serum lactate dehydrogenase and total bilirubin, while it was negatively correlated with haematocrit and fetal haemoglobin levels. CONCLUSION: Our study showed low prevalence of abnormal transcranial Doppler velocities and low prevalence is unrelated to low markers of haemolysis in our study population.